Efektivitas functional communication training dalam meningkatkan perilaku meminta pada anak dengan autism spectrum disorder - Detricia Tedjawidjaja; Fenny Hartiani (Jurnal Ilmiah Psikologi Terapan, 2021)
The current study aims to examine the effectiveness of functional communication training to increase asking behavior by exchanging pictures for children with an autism spectrum disorder. The participant in this study is a 6-years old girl with a diagnosis of Autism Spectrum Disorder with Intellectual Impairment. This study uses a single-subject design consisting of A-B-A phases. Functional communication training is implemented using the most-to-least prompting technique which is divided into 8 sessions. The result depicts that 84% of participants increase their ability to perform requesting behavior by exchanging pictures of the trials given. Furthermore, after the implementation of functional communication training, there is an increase in the frequency of requesting behavior by exchanging pictures at post-test (average 74%) and at follow-up (average 82%). Implications of this study indicate the importance of considering the function of problem behavior in training the appropriate communicative responses for children with an autism spectrum disorder.